Pelacakan Gangguan Kereta Komuter Melalui Twitter Crawling - Lya Hulliyyatus Suadaa (Jurnal Aplikasi Statistika & Komputasi Statistik, 2016)
Nowadays, Twitter is a very popular social media, especially in Indonesia. Tweets can be used as a data source to explore information. PT KAI (Kereta Api Indonesia) Commuter Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi) (PT KCJ) has an official account, Twitter @CommuterLine, to disseminate information related to commuter train. One of important information regularly published in @CommuterLine account are information about commuter train intrusion. PT KCJ uses specific tweet format and certain hashtag to inform people about the intrusion. Intrusion information that is usually published is time of the intrusion, name of the station, train number and train line. #InfoLintas and #InfoLanjut hashtag are used to easier tweet searching. Information extraction processes are adopted to automatically extract commuter train intrusion information from @CommuterLine account Twitter. The statistical analysis about commuter train tweets are visualized in tables and graphs. A prototype system in the form of mobile application is developed to track commuter train intrusion based on the result of the information extraction.